The Molecular Mechanisms Of Rapamycininduced Autophagy And Apoptosis In T-47d Breast Carcinoma Cells - Moad, Ahmed Ismail Hassan (2013)
Autophagy is an evolutionarily conserved lysosomal degradation pathway that leads to degradation of proteins and entire organelles and subsequently plays a crucial role in the homeostatic process of recycling proteins and organelles. Autophagy is an important biological mechanism that enables cell survival and to induce death of damage cells. There is increasing evidence that autophagy progresses to autophagic cell death when the process is over-stimulated. Functional relationships have been described between apoptosis (Type I cell death) and autophagic cell death (Type II cell death). However, the molecular relationships and the circumstances of which molecular pathways dictate the choice between autophagy and apoptosis are currently unknown. Autophagy is regulated by the mammalian target of rapamycin (mTOR) kinase pathway. The mTOR are known to inhibit the autophagy process and subsequently lead to tumor development. As a strategy, rapamycin, a known inhibitor of mTOR, was used as an autophagy inducer and 3-methyladenine (3MA) as a classical inhibitor of autophagy. In the present study, a systematic global gene expression was investigated in rapamycin-induced autophagy and the effects of rapamycin when autophagy process is inhibited. The findings have demonstrated that rapamycin was capable of inducing autophagy in T-47D breast carcinoma cells. However, when autophagy was inhibited by 3MA, rapamycin appeared to induce apoptosis in these breast cells.